Testing extractants for Cu, Fe, Mn, and Zn in tropical soils treated with sewage sludge for 13 consecutive years - Nogueirol, Roberta Corrêa; De Melo, Wanderley José [UNESP]; Alleoni, Luís Reynaldo Ferracciú (Springer Nature, 2013)
In this paper, we report on a field experiment being carried out in a Typic Eutrorthox. The experiment was initiated in the 1997-98 agricultural season as a randomized block design with four treatments (0, 5, 10, and 20 t ha -1) of sewage sludge and five replicates. Compound soil samples were obtained from 20 subsamples collected at depths of 0-0.1 and 0.1-0.2 m. Cu, Fe, Mn, and Zn concentrations were extracted with DTPA pH 7.3; 0.1 mol L -1 HCl, Mehlich-I, Mehlich-III, and 0.01 mol L-1 CaCl 2. Metal concentrations were determined via atomic absorption spectrometry. Diagnostic leaves and the whole above-ground portion of plants were collected to determine Cu, Fe, Mn, and Zn concentrations extracted by nitric-perchloric digestion and later determined via atomic absorption spectrometry. Sewage sludge application caused increases in the concentrations of soil Cu, Fe, and Mn in samples taken from the 0-0.1 m depth evaluated by the extractants Mehlich-I, Mehlich-III, 0.01 mol L-1 HCl and DTPA pH 7.3. None of the extractants provided efficient estimates of changes in Mn concentrations. The acid extractants extracted more Cu, Fe, Mn, and Zn than the saline and chelating solutions. The highest concentrations of Cu, Fe, and Zn were obtained with Mehlich-III, while the highest concentrations of Mn were obtained with HCl. We did not observe a correlation between the extractants and the concentrations of elements in the diagnostic leaves nor in the tissues of the whole maize plant (Zea mays L.). © 2013 Springer Science+Business Media Dordrecht.
Keywords: Micronutrients; Organic matter; Plant nutrition; Trace elements; Above grounds; Block designs; Field experiment; Metal concentrations; Mn concentrations; Tropical soils; Atomic absorption spectrometry; Biological materials; Grain (agricultural product); Iron compounds; Plants (botany); Sewage sludge; Soil testing; Tissue; Zinc; Manganese; chelating agent; copper; hydrochloric acid; iron; manganese; nitric acid; organic carbon; pentetic acid; perchloric acid; sodium chloride; zinc; atomic absorption spectroscopy; concentration (composition); sewage; sludge; soil organic matter; trace element; agriculture; atomic absorption spectrometry; concentration (parameters); controlled study; environmental management; maize; nonhuman; pH measurement; plant leaf; plant tissue; sludge treatment; soil acidity; soil analysis; soil depth; tropics; Zea mays